Transcendendo o ideário do arco-íris: da invisibilidade à efetivação de direitos - Silva, Marcos Valdir (2009)
This dissertation intends to expand the debate on the enforcement of rights involving the Lesbian, Gay, Bisexual and Transgender people, in a dialogue with the professional practice of social workers in the Reference Centers for Human Rights in the Prevention and Fight Against Homophobia. As the basis for the research I have reconstructed my life history, its interconnection with the trajectory of the Brazilian LGBT movement and the construction of identity as a professional and an activist. I have also tried to search for and tell the participation of social workers towards the possibility of enforcing LGBT rights. In order to achieve such purpose I have conducted in-depth reading of theoretical approaches to sexual diversity and discussed themes such as sexuality, heteronormativity, sexual orientation and the ethical/political project of professional social workers. These themes are of high importance to overcome the prejudice that still prevails in society to this day. But, as I believe advancements and achievements have been made, I have organized conceptions, terms and information through a documental and bibliographical research on the history of the LGBT movement, resulting in a database consisting of tables, charts and information concerning the legislation and the Reference Centers currently operating in Brazil. This search has allowed me to find people and their experiences and personal accounts, which then required the use of Oral History methodology. As they express their opinions and experiences I had the opportunity to know the reality of those who fight homophobia. Since the enforcement of rights is a result of the acknowledgment of demands and needs by the State, I listened to the accounts provided by social workers from the Reference Centers in Campinas and São Paulo, as they represent today new places for this professional category. An important aspect of this dissertation is the possibility of integrating the LGBT movement struggle with the agenda of the Social Workers´ Professional Councils statewide and nationwide in regard of the sexual orientation. Thus, I perceived that going beyond the rainbow ideas today is to contribute to overcome invisibility and provide opportunities to build rights that are equal to everyone regardless of their sexual orientation